Treatment of 2nd class division 1 malocclusion by using Herbs appliance - Nedeljković Nenad; Stamenković Zorana; Nikolić Predrag V. (Serbian Medical Society - Dental Section, Belgrade, 2005)
In this case was described the treatment in 14.5 years old female patient with II/1 class of malocclusion. On the base of clinical findings, study cast analysis, analysis of orthopan and profile cephalograms, there were assess II/1 class of malocclusion with deep bite, bimaxilar protrusion of frontal teeth and mild crowding in lower jaw. Patient was inefficacy treated by Andresen's activator for two years. This occasion and patients age was reason to continue with the therapy by Herbst appliance for 6 months and fixed appliance 7 months more. By Herbst appliance was corrected sagital relation between jaws in very short treatment time and continuing treatment with fixed appliance was corrected intermaxilar teeth relation.